Actions That Obstacle The Justice Process (Contempt Of Court) in The Criminal Law System in Indonesia - H. Yusep Mulyana (PT FORMOSA CENDEKIA GLOBAL, 2023)
In Law Number 1 of 2023 concerning the Criminal Code, especially Article 281, criminal acts against the court process (contempt of court) are punishable by imprisonment for a maximum of 1 year or a fine of up to 10 million rupiah. The actions included in the offense of contempt of court, among others, are aimed at anyone who: Does not comply with a court order or a judge's decision issued for the benefit of the judicial process. Being disrespectful to judges or the trial or attacking the integrity or impartiality of judges in court proceedings; or Unlawfully record, publish directly, or allow for publication anything that can affect the impartial nature of judges in court hearings. The environment of the court body must be able to become a legal institution that is trusted by the public. These events should be viewed from the perspective of the